SENSITIVITAS EKSTRAK BUAH MENGKUDU (Morinda citrifolia L.) TERHADAP BAKTERI Streptococcus agalactiae - Anzila Rizki W Muharram; Henni Syawal; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted from October to December 2014 in the Laboratory of Parasitic Diseases of Fish Faculty of Fisheries and Marine Sciences, and Laboratory of organic and natural material of Faculty of Mathematics and Natural Sciences, University of Riau, Pekanbaru. The purpose of this study to determine the concentration of noni fruit (Morinda citrifolia L.) that can inhibit the growth of Streptococcus agalactiae and safe dose to be given to the fish. The method that had been used was experimental method with concentration : P0: control, P1 (4%), P2 (5%), P3 (6%), P4 (7%), P5 (8%), P6 (9%), P7 (10%). The results show noni fruit solution to Streptococcus agalactiae sensitive average highest inhibition zone formed on treatment P7 (10%) of 9.83 mm and significantly different between treatments (P <0.05). MIC test of extract methanol Morinda citrifolia L. on treatment P2 (5%) of 78 x 108 cfu/mL. LD50 test solution for tilapia (Oreochromis niloticus) extract methanol Morinda citrifolia L. marinated for 24 hours after Reed and Muench analysis contained in the concentration of 1.42%.Key word: Morinda citrifolia L., Streptococcus agalactiae, Sensitivitas, MIC, LD50.